Did hydroclimate conditions contribute to the political dynamics of Majapahit? A preliminary analysis - Herho, Sandy; Herho, Katarina; Susanto, Raden (Geographica Pannonica, 2023)
Majapahit was the largest Hindu-Buddhist empire that ruled the Indonesian archipelago from the late 13th to mid-16th centuries CE. Only now there is still a lot of history surrounding the Majapahit era that has yet to be revealed. One is about how environmental factors influenced the political dynamics at that time. This study tries to discuss the influence of hydroclimate regimes using the Paleo Hydrodynamics Data Assimilation (PHYDA) product on the political history of Majapahit during the dry season, which occurs during the boreal summer. We conducted a spatial analysis of the area of drought by taking data from the Palmer Drought Severity Index (PDSI) in the Maritime Continent (MC) for six crucial episodes in the history of Majapahit, namely during the reign of Jayanegara (1309 - 1328 CE), which was marked by various political instability, the golden age of Majapahit (1309 - 1328 CE). 1350 - 1389 CE), the time of the Paregreg civil war (1405 - 1406 CE), the great famine event (ca. 1426 CE), the candrasengkala event (1478 CE), and in 1527 CE, which was marked by the complete conquest of Majapahit by the Demak sultanate. The results show statistically significant differences in most of these six episodes (except during the heyday of Majapahit) against the reference period, which is the average PDSI over the entire Majapahit era (1293 - 1527 CE). In addition, we also conducted a temporal analysis linking PDSI with shifts in the West Pacific Inter Tropical Convergence Zone (WP ITCZ) and El Niño Southern Oscillation (ENSO) represented by Niño 3.4 Sea Surface Temperature (SST). This temporal analysis results show a positive correlation between WP ITCZ - PDSI, a negative correlation between Niño 3.4 SST - PDSI and a negative correlation between ITCZ - Niño 3.4 SST. All of these correlations are statistically significant. So the probable cause of dry/wet conditions in MC during the Majapahit era was triggered by a meridional ITCZ shift which triggered different ENSO phases through Bjerknes feedback. This preliminary study has implications as opening the way to understand the influence of environmental factors on political conditions in the Majapahit era in more detail.
Keywords: Drought; ENSO; Majapahit; PDSI; Pluvial